Comparison of pre- and postoperative brain MRI findings of neonates undergoing congenital heart surgery- The impact of brain injury scores on long-term neurological outcome - Kuhn, Viktoria Anna; Justus Liebig University Giessen (My University, 2022)
Objectives: To determine the impact of surgical and therapeutic risk factors on pre- and postoperative brain MRI findings and to evaluate the association of patient characteristics, perioperative risk factors and brain imaging abnormalities on neurologic outcome in patients with hypoplastic left heart syndrome (HLHS) or d-transposition of the great arteries (d-TGA) who underwent cardiac surgery including cardiopulmonary bypass as neonates. Methods: We performed a retrospective analysis to identify neonates with HLHS and D-TGA who underwent cardiac surgery at a single center between 2009 and 2017. Patients born <36 weeks’ gestation, those with genetic abnormalities known to be associated with abnormal neurodevelopment, congenital brain abnormalities or multiple congenital anomalies were excluded. Andropoulos’ Brain Injury Scores were calculated from pre- and postoperative brain magnetic resonance images (MRI). Patient characteristics, perioperative risk factors and brain MRI findings were correlated to outcome assessments performed on patients between 5 months and 2 years of age. Neurologic deficits were quantified using the Pediatric Stroke Outcome Measure (PSOM) and functional outcome was evaluated using the Pediatric Version of the Glasgow Outcome Scale–Extended (GOS-E). The risk factors for worse neurodevelopmental outcome were assessed using multivariate logistic regression. Results: Twenty-four neonates with HLHS and twenty-nine neonates with D-TGA were identified and met our enrollment criteria. Preoperative brain MRI was abnormal in 53% of the patients and postoperative MRI findings were abnormal in 72% of the patients. Both groups showed a significant upward change in median total brain injury score from the preoperative to postoperative study (HLHS: p=0.006; d-TGA p=0.017). Duration of ventilation more than 12 days and deep hypothermic circulatory arrest (DHCA) longer than 40 minutes were associated with worse PSOM and GOS-E scores. MRI measures of brain injuries were not associated with worse outcome by PSOM or GOS-E. Conclusion: For HLHS and d-TGA patients, duration of mechanical ventilation and DHCA are associated with adverse neurologic outcome. Neonatal brain MRI commonly demonstrates acquired brain injuries, but the clinical impact of these abnormalities are not often seen before 2 years of age.
Keywords: Congenital heart disease; Neurological Outcome; Congenital heart surgery; Brain injury; Magnetic resonance imaging; Neurodevelopmental Outcome; ddc:610